Being there : learning to live cross-culturally - Davis, Sarah H.; Konner, Melvin (Harvard University Press, 2011)
As they immerse themselves in foreign cultures, trained anthropologists find that accepting difference is one thing, experiencing it is quite another. In tales that entertain as well as illuminate, these writers show how the moral and intellectual challenges of living cross-culturally revealed to them the limits of their perception and understanding.